PEMBERIAN FLY ASH (ABU SISA BOILER PABRIK PULP) UNTUK MENINGKATKAN pH TANAH GAMBUT - -, Rini; Nurdin, Hazli; Suyani, Hamzar; Prasetyo, Teguh B. (Universitas Andalas, 2009)
Vol. 2, No. 2ABSTRACT The research of fly ash as ameliorant to decrease the humic acid in peat soil of Rimbo Panjang, Riau. It is found that fly ash at 10 ton/Ha showed the best result decresing pH of peat soil (4.4 to 6.36) and humic acid content (0.2923 g/g to 0.0972 g/g). Keywords: fly ash, peat soil, pH, humic acid